PENGARUH PROMOSI PENJUALAN DAN HARGA TERHADAP KEPUTUSAN KONSUMEN DALAM PEMBELIAN MOBIL MEREK TOYOTA PADA PT DELTAMAS SURYA INDAH MULIA - Karim, Alfin; na, Iva; Putra, Eka; Wiselee, Calvin; Filbert Wijaya, Vinrick; bert, Al (Aksara Public, 2019)
The objective of the research is to examine and analyze the effect of sales promotion and pricing on customer decision partially and simultaneously. The data analysis was performed by multiple linear regression analysis. This research uses a quantitative approach, this type of research was a quantitative descriptive and the research nature of this study was cumulative causal. The research populations were 3080 customers. The samples were drawn using a slovin technique so that the samples used for regression test were 154 respondents and 30 respondents were used for validity and reliability testing of customers at PT Deltamas Surya Indah Mulia The results show that simultaneously, sales promotion and pricing have a positive and significant effect on the employee performance in which F-count (32,274)> F-table (2,66) with significant level of 0,000 <0.05). Partially, sales promotion with the value of t-count 3,098> t-table 1, 97580 with significant level of ( 0,002 <0,05) and pricing with t-count of 4,862> t-table 1.97580 with significant level of ( 0,000 <0,05) had a positive and significant effect on the customer’s decision. The result of determination coefficient test show that 29% from variation of dependent variable of customer’s decision can be affected by sales promotion and pricing and the remaining 71% can be explained by this variation not mentioned in this research as motivation of work, compensation, and so forth.